Evolutionary Biology: Genome Evolution, Speciation, Coevolution and Origin of Life - Pontarotti, Pierre (Springer International Publishing : Imprint: Springer, 2014)
This book includes the most essential contributions presented at the 17th Evolutionary Biology Meeting in Marseille, which took place in September 2013. It consists of 18 chapters organized according to the following categories: ·         Molecular and Genome Evolution ·         Phylogeography of Speciation and Coevolution ·         Exobiology and Origin of Life The aims of the annual meetings in Marseille, which bring together leading evolutionary biologists and other scientists using evolutionary biology concepts, e.g. for medical research, are to promote the exchange of ideas and to encourage interdisciplinary collaborations. Offering an overview of the latest findings in the field of evolutionary biology, this book represents an invaluable source of information for scientists, teachers and advanced students.